Tasawuf, Maqomat Wa Ahwal Serta Perkembangannya Dalam Dunia Islam - R, Rian; Abbas, Nurlaelah; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to comprehensively describe the understanding of Sufism, the development of Sufism, and the concepts of maqamat and ahwal as two main pillars in the spiritual journey of a Sufi. This research employs a qualitative method with a library research approach through the examination of primary and secondary references, including books, scientific articles, and relevant journals. The findings of this study indicate that maqamat represents spiritual stages achieved through mujahadah (spiritual struggle) and riyadhah (spiritual discipline) in a gradual manner, while ahwal refers to spiritual states granted directly by Allah and are temporary in nature. Both concepts play a crucial role in the process of a servant's approach to their Lord. The development of Sufism from the early ascetic phase to the contemporary period demonstrates the systematic strengthening of maqamat and ahwal as pathways to attain ma'rifatullah.